2015
DOI: 10.23937/2572-3278.1510006
|View full text |Cite
|
Sign up to set email alerts
|

Active Hexose Correlated Compound Activates Immune Function to Decrease Chlamydia trachomatis Shedding in a Murine Stress Model

Abstract: A cold-induced stress mouse model for investigating chlamydia genital infection and immune response analysis was established in our laboratory. Previous results showed that cold-induced stress results in suppression of the immune response and increased intensity of chlamydia genital infection in the mouse model. The purpose of the present study was to evaluate the potential therapeutic value of active hexose correlated compound (AHCC) against chlamydia genital infection in mice. AHCC is an extract of mushroom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…We recently reported the promotion of Th 1 and 17 cells, which predominantly produced IFN-γ and IL-17, respectively, by AHCC® through inducing IL-1β production from monocytes in humans [20]. In accordance with this 3 Journal of Immunology Research finding, the culture supernatants of AHCC®-treated murine monocytic J744.2 cells promoted the production of TNF-α from splenic T cells of mice [12] while AHCC® induced IL-8 production from human myelocytic THP-1 cells via activating mitogen-activated protein kinases (MAPKs) and NF-κB pathways [14]. In a mouse study, AHCC® administration increased cytokine production in the intestine fluid dependently of TLR2 and TLR4, suggesting the implication of these molecules in AHCC®-mediated immune modulation [52].…”
Section: T Cell Immune Responses T Cells a Component Of The Adaptivsupporting
confidence: 67%
See 1 more Smart Citation
“…We recently reported the promotion of Th 1 and 17 cells, which predominantly produced IFN-γ and IL-17, respectively, by AHCC® through inducing IL-1β production from monocytes in humans [20]. In accordance with this 3 Journal of Immunology Research finding, the culture supernatants of AHCC®-treated murine monocytic J744.2 cells promoted the production of TNF-α from splenic T cells of mice [12] while AHCC® induced IL-8 production from human myelocytic THP-1 cells via activating mitogen-activated protein kinases (MAPKs) and NF-κB pathways [14]. In a mouse study, AHCC® administration increased cytokine production in the intestine fluid dependently of TLR2 and TLR4, suggesting the implication of these molecules in AHCC®-mediated immune modulation [52].…”
Section: T Cell Immune Responses T Cells a Component Of The Adaptivsupporting
confidence: 67%
“…Of the oligosaccharides in AHCC®, about 20% are α-1,4-glucans, of which a proportion is partially acylated, with a mean molecular weight around 5000 Daltons [6,7]. The effects of AHCC® on immune cells of humans and animals were reported in in vitro and in vivo studies, suggesting the possible help of its supplementation in defending the host against infections and malignancies via modulating the immune system [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. This review focuses on the reported effects of AHCC® on natural killer (NK) and T cells given their roles in host defense and inflammation [29][30][31][32][33][34], providing a platform for the better understanding of immune-mediated mechanisms and clinical implications of AHCC® and possibly other medical mushrooms in health and disease.…”
Section: Introductionmentioning
confidence: 99%
“…Because AHCC can activate monocytes and monocytic cell lines [13,26,27] and because AML blasts are immature myeloid-lineage cells, we sought to determine whether AHCC could directly affect blast-cell survival and proliferation. We began by testing AHCC against the MV4-11 cell line, which contains the FLT3-ITD mutation shared by approximately 20% of AML patients [28] and is linked to increased risk of relapse and mortality [29].…”
Section: Resultsmentioning
confidence: 99%
“…For example, it prolongs survival in advanced liver cancer patients [19], enhances the antitumor activity of 5-fluorouracil [41], and reduces tumor burden alone and in combination with CpG oligodeoxynucleotides in a murine melanoma model [17]. It shows immune-modulatory effects as well such as serving to sooth hapten-induced colitis in rats [42], to decrease bacterial burden [43], and to enhance resistance to pathogens such as Chlamydia trachomatis in murine models of stress [26]. As such, AHCC may not only aid in the clearance of AML blasts, it may also help reduce the incidence of infections in these typically immune-compromised patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation